MEASURING DIGITAL LITERACY SKILLS AMONG STUDENTS IN SENIOR HIGH SCHOOL - Fitra Delita; Nurmala Berutu; Tumiar Sidauruk; Elfayetti Elfayetti; Herdi Herdi (Universitas Negeri Medan, 2022)
Various digital-based learning media strongly support the quality of online learning. Digital media is essential in the learning process because it can package the material into more contextual, interesting audiovisual, reduces verbalism, and is more interactive. The primary purpose of this research was to measure the differences in digital literacy by comparing the digital learning media and PowerPoint media in online learning. The design of this study was a pretest-posttest group with a quasi-experimental method. Overall, 56 students in a senior high school in Senior High School 2 Percut Sei Tuan, Medan City, Sumatera Utara Province, served as participants in this study. Data were collected by questionnaires and structured interviews for digital literacy. Data analyses were mixed with the quantitative and qualitative methods. Quantitative data were analyzed statistically through independent samples t-test, and qualitative data were analyzed descriptively. Digital literacy data were analyzed using SPSS version 24 software. The results showed that the students' digital literacy using digital learning media was superior to those prepared using PowerPoint. Based on each aspect of digital literacy, namely, internet searching, understanding, and utilizing digital devices, hypertextual navigation, content evaluation, creating digital content, and communicating information, there were significant differences between groups on digital literacy competencies. All aspects of digital literacy in the experimental class were higher than in the control classKeywords: Digital Literacy, E-Learning, Learning Media